Pengaruh Ekstrak Mikroalga sebagai Biostimulan pada Induksi Kalus Kopi Arabika (Coffea arabica L.) - Patria Prasasya; Sutini; Saefur Rohman (Postgraduate, University of Mataram, 2026)
Arabica coffee (Coffea arabica L.) is an economically important plantation crop in Indonesia, but its productivity is still relatively low. The purpose of this study was to influence Chlorella vulgaris extract as a biostimulant on in vitro callus induction using Arabica coffee leaf disc explants. The study method used a completely randomized design with six Murashige and Skoog (MS) media formulations consisting of synthetic plant growth regulator (PGR) (2,4-D and kinetin), 15% and 20% Chlorella vulgaris extract, and a combination of microalgae extract with PGR. The parameters observed included the percentage of explants with callus, color and texture, and explant contamination. The results and discussion of the media formulation significantly affected callus induction, while contamination was not significantly affected. PGR media and 15% Chlorella vulgaris extract treatment produced comparable callus formation percentages, indicating that microalgae extracts were as effective as synthetic PGRs in supporting early callus induction. Most of the calli were yellow to greenish in color with a compact texture, indicating the suitability of the callus induction stage, although further optimization is needed to obtain easily disintegrated calli for subsequent somatic embryogenesis. The conclusion shows the potential of Chlorella vulgaris extract as an environmentally friendly biostimulant for Arabica coffee tissue culture.